2011
DOI: 10.1371/journal.pone.0020525
|View full text |Cite
|
Sign up to set email alerts
|

H2S Donor, S-Propargyl-Cysteine, Increases CSE in SGC-7901 and Cancer-Induced Mice: Evidence for a Novel Anti-Cancer Effect of Endogenous H2S?

Abstract: BackgroundS-propargyl-cysteine (SPRC), an H2S donor, is a structural analogue of S-allycysteine (SAC). It was investigated for its potential anti-cancer effect on SGC-7901 gastric cancer cells and the possible mechanisms that may be involved.Methods and FindingsSPRC treatment significantly decreased cell viability, suppressed the proliferation and migration of SPRC-7901 gastric cancer cells, was pro-apoptotic as well as caused cell cycle arrest at the G1/S phase. In an in vivo study, intra-peritoneal injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 31 publications
4
73
2
Order By: Relevance
“…Our research (31) and other studies (24)(25)(26)(27)(28)(29)(30) suggest that H 2 S is beneficial for cancer cells growth, proliferation, migration and invasion. On the contrary, some other researchers found that H 2 S exerted potential anticancer efficiency in SGC-7901 gastric cancer cells (40), oral cancer cell lines (41), colon cancer cells (42), and in several different human cancer cell lines (HeLa, HCT-116, Hep G2, HL-60, MCF-7, MV4-11 and U2OS) (43). As the above is contradictory further research must be carried out to clarify these issues.…”
Section: Discussionmentioning
confidence: 92%
“…Our research (31) and other studies (24)(25)(26)(27)(28)(29)(30) suggest that H 2 S is beneficial for cancer cells growth, proliferation, migration and invasion. On the contrary, some other researchers found that H 2 S exerted potential anticancer efficiency in SGC-7901 gastric cancer cells (40), oral cancer cell lines (41), colon cancer cells (42), and in several different human cancer cell lines (HeLa, HCT-116, Hep G2, HL-60, MCF-7, MV4-11 and U2OS) (43). As the above is contradictory further research must be carried out to clarify these issues.…”
Section: Discussionmentioning
confidence: 92%
“…For these reasons, we have excluded the combined molecules mentioned earlier from our present analysis. In another study, Ma et al report on the anticancer effect of the garlic extract component S-propargylcysteine (72). Although this compound is often discussed as a H 2 S pathway modulator, its pharmacological profile is extremely complex, as it includes kinase activation, up-regulation of CSE, and many other actions (9,72).…”
Section: H 2 S Donation Versus H 2 S Biosynthesis Inhibition In Cancermentioning
confidence: 99%
“…In another study, Ma et al report on the anticancer effect of the garlic extract component S-propargylcysteine (72). Although this compound is often discussed as a H 2 S pathway modulator, its pharmacological profile is extremely complex, as it includes kinase activation, up-regulation of CSE, and many other actions (9,72). Thus, while the compound can induce apoptosis in vitro and may reduce tumors in vivo, we believe that its actions are too complex to be evaluated in the current review.…”
Section: H 2 S Donation Versus H 2 S Biosynthesis Inhibition In Cancermentioning
confidence: 99%
“…It has been reported that the increased H 2 S production plays a crucial role in cell proliferation and the related angiogenesis in several types of cancer cell lines, such as colonic and ovarian cancers. 18,19) In addition, there are many papers showing that endogenous or exogenous H 2 S modulates cell proliferation and migration in gastric, oral, breast, pancreas, lung or prostate cancer and also leukemia, 12,[20][21][22] whereas, H 2 S promotes and suppresses cancer growth in distinct cells. Thus, the effects of H 2 S on cancers might vary with the tissues, conditions surrounding cancer, the amount of synthesized H 2 S, and so on.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, there are inconsistent papers concerning the effects of H 2 S on gastric cancer cell proliferation and related angiogenesis. 12,13) In the present study, we evaluated the role of endogenous H 2 S in gastric cancer proliferations in human gastric cancer AGS cells. Our results showed that endogenous H 2 S synthesized by CSE promotes the proliferation of AGS cells, most probably through inhibition of apoptosis.…”
mentioning
confidence: 99%